An Analysis Of Students Grammatical Error In Writing Descriptive Paragraph Made By The Eighth Grade Students Of Smp Negeri 2 Karanganyar - Mitsalina, Endah; Susi, Yayu; Pratiwi, Berlin Insan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
English is taught as a compulsory subject in junior high school, senior high school and also in universities for several terms. So that the students must have English skill. There are differences of rule and structure in English and Indonesian. For instance, in Indonesian here is no change in verb and it is very different with English. Mostly, Indonesian is still influenced by their mother tongue on the approach to the target language (English). Therefore, this research aimed to find out the student’s grammatical error in writing descriptive paragraph. The objectives of this research are as follows: 1) To find the students grammatical error in writing descriptive paragraph made by the eighth-grade students of SMP Negeri 2 Karanganyar. 2) To find out and give image to readers of the most frequent errors that the students do in writing descriptive paragraph made by the eighth grade of SMP Negeri 2 Karanganyar. This research was presented using descriptive qualitative research method. The researchers used a documentation as instrument for collecting the data. The researchers took one assignment in students’ English task books. In collect data, the researchers did some steps. 1) Ask for permission to the teacher for taking documentation the students’ tasks. 2) Consulting the task to the teacher. 3) Giving the task. 4) Analysing the student tasks. 5) Getting the data. The data was collected on 14th June 2021. The population of this study was taken from the eighth-grade students SMP Negeri 2 Karanganyar and the researchers took five class (VIII A, VIII B, VIII C, VIIID, and VIIIE) as the subject. The sample was taken by using purposive sampling technique. The class consisted of 30 students. The result of this research shows that the total errors are 100%. It means that the grammatical error in writing descriptive paragraph made by the eighth grade of SMP Negeri 2 Karanganyar is on less sufficient level. The percentage of students’ grammatical error in types of omission (29,5%), error of addition (16,7%), error of misformation (44,9%) and error of misordering (8,9%). Based on the result of the research, it is suggested that the eighth-grade students of SMP Negeri 2 Karanganyar should be given more explanation and exercise in writing descriptive paragraph. Keywords: Error Analysis, Grammatical Error, Paragraph, Writing